In vitro litholytic activity of some medicinal plants on urinary stones - L. Yachi; S. Bennis; Z. Aliat; A. Cheikh; M.O.B. Idrissi; M. Draoui; M. Bouatia (African Journal of Urology, 2018)
Objective: This study was designed to evaluate the effect of plant extracts used in traditional medicine on the dissolution of three types of kidney stones. Subjects and methods: Kidney calculi of cystine; uric acid and pure carbapatite were incubated in vitro during 6 weeks in the presence of three of plant extracts and of 0.9% NaCl solution used as control. An extract of each plant was prepared by infusion of three grams of powdered plants during 30 min in 100 mL of a boiled NaCl 0.9% aqueous solution. Each extract was then filtered and thereafter set in a flask containing a stones. At the end of each week the stone was removed from the experimental medium and weighted after a 18 h drying at 40 °C. Results: After 6 weeks of experiment and with in vitro study, we are observed that the aqueous extract of the seeds of Trigonella foenum-graecum has a better effect on dissolution of cystine and carbapatite stones (p < 0.05), with mass loss of 94 mg and 73 mg respectively at the end of experiment. While with NaCl solution, the mass was small. Conclusion: Our experiment failed to demonstrate a significant effect of the tested plant extracts to dissolve three types stones in vitro. However, we observed that only the extract of the seeds of T. foenum-graecum has a better effect on dissolution of cystine and carbapatite stones probably resulting from formation of complexes between stones and polyphenols or flavonoids present in the extracts. Keywords: Urinary stones, Litholytic activity, Trigonella foenum-graecum, Petroselinum crispum, Opuntia ficus-indica